2018
DOI: 10.1007/s00068-018-1009-5
|View full text |Cite
|
Sign up to set email alerts
|

Long-term follow-up after rib fixation for flail chest and multiple rib fractures

Abstract: We show that rib fixation is a safe procedure and that patients reported a relative good quality of life. Patients should be counseled that after rib fixation approximately half of the patients will experience implant-related irritation and about one in ten patients requires implant material removal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
2
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 47 publications
(67 citation statements)
references
References 29 publications
1
59
2
1
Order By: Relevance
“…Of this latter group > 70% recovers to an acceptable level [17]. This also holds true for instance for patients with specific injuries like rib fractures, hand-or wrist injuries or complex foot injuries [29][30][31].…”
Section: The Evolution Of Mortality In Traumamentioning
confidence: 98%
“…Of this latter group > 70% recovers to an acceptable level [17]. This also holds true for instance for patients with specific injuries like rib fractures, hand-or wrist injuries or complex foot injuries [29][30][31].…”
Section: The Evolution Of Mortality In Traumamentioning
confidence: 98%
“…Beks et al 8 reported as long-term results that 48% of their patients had implant-related irritation and 9% required implant removal. In the present study, irritation was also reported by some patients, but the incidence rate was approximately 10% among the patients followed up.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, there are few studies evaluating the long-term outcomes or complications of patients undergoing rib fixation, although some studies have described the long-term assessment of factors such as irritation or quality of life of these patients. 8 9 16–18 Importantly, these past studies have small sample sizes, their follow-up rates are limited to only about 50% of the patients, and the follow-up duration is within several months up to 1 year.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As short-term results in many studies show favorable results, there is only scarce information of the long-term results of fixation of rib fractures. In a long-term follow-up study by Beks et al, patient-reported outcomes were also studied in patients several years after rib fixation [6]. They show that rib fixation is a safe procedure and that patients reported a relative good quality of life.…”
Section: Dear Colleaguesmentioning
confidence: 99%